2011
DOI: 10.1242/jcs.058438
|View full text |Cite
|
Sign up to set email alerts
|

BIMEL, an intrinsically disordered protein, is degraded by 20S proteasomes in the absence of poly-ubiquitylation

Abstract: BIM-extra long (BIMEL), a pro-apoptotic BH3-only protein and part of the BCL-2 family, is degraded by the proteasome following activation of the ERK1/2 signalling pathway. Although studies have demonstrated poly-ubiquitylation of BIMEL in cells, the nature of the ubiquitin chain linkage has not been defined. Using ubiquitin-binding domains (UBDs) specific for defined ubiquitin chain linkages, we show that BIMEL undergoes K48-linked poly-ubiquitylation at either of two lysine residues. Surprisingly, BIMELΔKK, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 60 publications
(84 reference statements)
0
52
0
Order By: Relevance
“…This is the first demonstration that a BCL-2 family member can be degraded by 26S proteasomes in an Ub-independent manner, and raises the possibility that other BH3-only proteins containing unstructured regions may be degraded in a similar manner in vivo, 29 In more general terms, there is an expanding list of unstructured proteins including p53, p73a, p21 Cip1 IkB, MCL-1 and BIM that are proposed 20S proteasome substrates based on in vitro studies. 12,14,15,22 Our studies with NOXA suggest that some of these proteins may be bona fide 26S proteasome substrates in vivo. For example, although MCL-1 can be degraded by 20S proteasomes in vitro and a non-ubiquitinated MCL-1 mutant is degraded at a similar rate compared with wild-type MCL-1, 15 other studies and our data suggest that 26S proteasomes have an important role in MCL-1 turnover in cells, possibly by the E3 ligase, MULE 30 ( Figure 4 and Supplementary Figure S6).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This is the first demonstration that a BCL-2 family member can be degraded by 26S proteasomes in an Ub-independent manner, and raises the possibility that other BH3-only proteins containing unstructured regions may be degraded in a similar manner in vivo, 29 In more general terms, there is an expanding list of unstructured proteins including p53, p73a, p21 Cip1 IkB, MCL-1 and BIM that are proposed 20S proteasome substrates based on in vitro studies. 12,14,15,22 Our studies with NOXA suggest that some of these proteins may be bona fide 26S proteasome substrates in vivo. For example, although MCL-1 can be degraded by 20S proteasomes in vitro and a non-ubiquitinated MCL-1 mutant is degraded at a similar rate compared with wild-type MCL-1, 15 other studies and our data suggest that 26S proteasomes have an important role in MCL-1 turnover in cells, possibly by the E3 ligase, MULE 30 ( Figure 4 and Supplementary Figure S6).…”
Section: Discussionmentioning
confidence: 75%
“…Our results suggested that NOXA is an unstructured protein that can be efficiently degraded in an Ub-independent manner (Figures 1 and 2, Supplementary Figures S4 and S5). Although several proteins containing unstructured regions, including p53, p73a, p21 Cip1 IkBa, MCL-1 and BIM, can be degraded in an Ub-independent manner by 20S proteasomes in vitro, 12,14,15,22 it remains to be demonstrated whether 20S proteasomes are required for their degradation in vivo. The CDK inhibitors p21 Cip1 and p19 Arf and the lysine-less protein p16 Ink4a can be degraded in an Ub-independent manner in vivo by proteasomes capped with alternate REGg activator subunits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because all these proteins are also degraded by the 26S proteasome in highly regulated processes, degradation through the NQO1-dependent pathway must occur under unique and still to be determined conditions. Another protein that has been reported to be degraded by the 20S proteasome without prior ubiquitylation is BIM-extra long [BIM(EL)], an intrinsically disordered protein that is a member of the BCL2 family (Wiggins et al, 2011). Inhibitor of  light chain gene enhancer in B cells alpha (IB) has also been shown to be degraded by the core 20S proteasome in a ubiquitinindependent manner, and its degradation could be protected by the expression of the p65 subunit of NF-B (Alvarez-Castelao and Castano, 2005;Kroll et al, 1997).…”
Section: Ubiquitin-independent Degradationmentioning
confidence: 99%
“…The 20S proteasomal degradation is a widespread phenomenon; since more than 30% of total cellular proteins possess substantial intrinsic structural disorders, they may be undergoing 20S proteasome-mediated degradation 19,22 . 20S proteasomal degradation is a passive process that only needs unstructured regions in the substrate protein 20 .This pathway is reported to promote the degradation of many key cellular proteins such as p53, p73, p21, PGC1-a, BIMEL and so on that possess unstructured regions [23][24][25][26] . The process is primarily controlled by NADH-bound NAD(P)H:quinine oxidoreductase 1(NQO1), which associates with 20S proteasome and inhibits this pathway 20,27 .…”
mentioning
confidence: 99%